Anti-Tuberculosis Therapy after DRESS: Case Report - Wahyuni, Dwi; Mulya, Deshinta Putri; Retnowulan, Heni (Acta Interna The Journal of Internal Medicine, 2021)
Introduction.Anti-tuberculosis-induced DRESS (drug reaction with eosinophilia and systemic symptoms) is uncommon, and usually delayed in diagnosis. The patient has minor complain and the clinical presentation involves the side effect on their heart and skin. Antituberculosis-related DRESS may have been present, but it has been underdiagnosed and underreported for several years. Management including discontinuation of the suspected drugs and changing it with second line treatment become less effective. Identifying the causative drug in DRESS is very difficult, especially in antituberculosis drugs.Case. A 34-year-old woman complains of having itch and redness throughout the body and fever. Two months before hospitalization, the patient was diagnosed with tuberculosis based on GeneXpert examination. Patients were given anti-tuberculosis drug therapy (OAT) which was 4 fixed drug combinations (FDC). Two weeks after taking the drugs, complains appeared. After 3 weeks the drug was stopped and in the next 1 week the patient's condition got worse, with itching and redness of the whole body accompanied by fever. Patients received treatment for 13 days with 125 mg/24-hour methylprednisolone therapy gradually reduced with OAT therapy levofloxacin 500 mg/24 hours and streptomycin 1 gram/24-hour IM (intramuscular).Conclusion. DRESS triggered by OAT was very rare and underreported. The choice of therapy after DRESS needed to be well considered, because it increased the risk for a DRESS to return with more severe manifestations when re-administering the same drug. The management in tuberculosis patients with a history of DRESS was given with second-line OAT with treatment options based on the clinician's experience.